MTEFs and Fiscal Performance : Panel Data Evidence - Grigoli, Francesco; Mills, Zachary; Verhoeven, Marijn; Vlaicu, Razvan (World Bank, Washington, DC, 2013)
In the last two decades more than 120 countries have adopted a version of a Medium-Term Expenditure Framework (MTEF). These are budget institutions whose rationale it is to enable the central government to make credible multi-year fiscal commitments. This paper analyzes a newly-collected dataset of worldwide MTEF adoptions during 1990-2008. It exploits within-country variation in MTEF adoption in a dynamic panel framework to estimate their impacts. The analysis finds that MTEFs strongly improve fiscal discipline, with more advanced MTEF phases having a larger impact. Higher-phase MTEFs also improve allocative efficiency. Only top-phase MTEFs have a significantly positive effect on technical efficiency.